The king's justice - MacNeal, Susan Elia (MacNeal, Susan Elia. Maggie Hope mystery, 2020)
"London. December, 1942. As the Russian army repels German forces from Stalingrad, Maggie Hope, secret agent and spy, takes a break from the Special Operations Executive division to defuse bombs in London. But Maggie herself is like an explosion waiting to happen. Shaken by a recent case, she finds herself living more dangerously--taking more risks than usual, smoking again, drinking gin and riding a motorcycle--and the last thing she wants is to get entangled in another crime. But when she's called upon to look into a stolen Stradivarius, one of the finest violins ever made, Maggie finds the case too alluring to resist. Meanwhile, there's a serial killer on the loose in London and Maggie's skills are in demand. Little does she know that in the process of investigating this dangerous predator, she will come face to face with a new sort of evil...and discover a link between the precious violin and the murders no one could ever have expected"--